ARE THERE CHANGES IN ORBICULARIS ORIS MUSCLE ACTIVITY DUE TO THE CONVENTIONAL PROSTHETIC TREATMENT OF COMPLETE EDENTATION ? - Popsor, S.; Soaita, Claudia (European Scientific Journal, ESJ, 2013)
Introduction. It is well known that the orbicularis oris muscles, in association with m.buccinator and m. pharyngeal constrictor, form a well defined functional unit, called the „buccinator mechanism‟, with important role in some orofacial functions. It is also involved in the ˝neutral zone″ establishment, as essential feature of complete edentation treatment. The purpose of this investigation was to assess the changes in clinical and electromyographic activity of orbicularis oris muscle (OO) in complete edentulous patients before and after the insertion of dentures. Material and method. Seven patients were included in this study. Electromyographic records of the upper(OOS) and lower(OOI) orbicularis oris muscle were made using the BioEMG II (Bioresearch Assoc.Inc.) surface electromyography device, performed at rest, while whistling and sucking before and 3 days after the insertion of the complete dentures. Results. There was a significant difference between OOS and OOI activity before inserting dentures in all three conditions (p =0.0156) as well as after the prosthesis insertion during sucking and whistling, a more pronounced activity of OOI being obvious. No statistically significant difference in the activity of the mentioned muscle groups before and after insertion of the dentures, in the three recording conditions was observed. Conclusion. Within the limits of the present study, we conclude that in terms of EMG at rest as well as during functional moments of sucking or whistling there are no significant changes in OOI and OOS muscle tone, before and after conventional prosthetic treatment of complete edentation.